Polymer membrane material as well as preparation method and application thereof

By performing in-situ polymerization and crosslinking network formation in polymer membrane materials, the problem of insufficient hydrophilicity of existing membrane materials is solved, and an ultrafiltration membrane with high selectivity and stability is achieved, which improves its application performance .

CN119455705AActive Publication Date: 2025-02-18TIANJIN POLYTECHNIC UNIV

Patent Information

Application Number
CN202510052063.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-18
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The existing polymer membrane materials have low hydrophilicity during use, resulting in low permeability, poor selectivity and easy scaling, which limits the application and development of ultrafiltration membranes.

Method used

By polymerizing alkenyl hydrophilic monomers and alkenyl siliconoxy monomers with film-forming polymers in situ in the cast film liquid, a functional polymer is formed and formed during the phase separation process by coupling agents The cross-linking network of chemical bonds locks in hydrophilic modifiers and improves the selectivity and stability of membrane materials.

Benefits of technology

It achieves high selectivity and stability of polymer film materials, improves its hydrophilicity and stain resistance, and extends the service life of ultrafiltration membranes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455705A_ABST
    Figure CN119455705A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of filtering membrane materials, and particularly relates to a polymer membrane material as well as a preparation method and application thereof. The polymer film material provided by the invention is prepared from the following preparation raw materials in percentage by mass: 10 to 18 percent of film-forming polymer, 0.1 to 22 percent of alkenyl monomer, 0.1 to 3 percent of initiator, 0.1 to 22 percent of coupling agent and 35 to 89.7 percent of organic solvent, the alkenyl monomer comprises an alkenyl hydrophilic monomer and an alkenyl siloxy monomer. The polymer formed by the alkenyl monomer through in-situ polymerization is physically wound with the film-forming polymer, so that the hydrophilicity and pollution resistance of the polymer film material are improved; the coupling agent is pre-embedded in a membrane casting solution to serve as a subsequent reaction anchor point, the coupling agent can serve as a uniformly-distributed network node to be quickly coupled and crosslinked through chemical action in the phase separation curing process, and a hydrophilic modifier easy to segregate and dissolve out is locked in the polymer membrane by taking covalent acting force as internal driving force for inhibiting segregation, so that the stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of filtration membrane materials, and in particular relates to a polymer membrane material and a preparation method and application thereof. Background Art

[0002] At present, separation technology based on ultrafiltration membranes is widely used in the water treatment industry; polyvinyl chloride, polyvinylidene fluoride, polyethersulfone, etc., as membrane materials of ultrafiltration membranes, have excellent chemical and thermal stability and good mechanical strength. However, due to the low hydrophilicity of these membrane materials themselves, problems such as low permeation flux, poor selectivity and easy scaling will occur during their use, which seriously limits the application and development of ultrafiltration membranes.

[0003] Therefore, it is necessary to modify the existing polymer membrane materials to improve their hydrophilicity; the common modification method at present is mainly surface segregation technology. Surface segregation is to add hydrophilic additives to the casting solution by blending. During the film forming process, driven by thermodynamics, the hydrophilic groups will be enriched and segregated on the film-forming surface. However, most of the existing hydrophilic additives are water-soluble polymers, which will precipitate into the coagulation bath to form pores with the exchange of non-solvents during the film forming process, which will significantly reduce the selectivity of the ultrafiltration membrane; in addition, there is a lack of stable chemical bonds between the hydrophilic additives and the polymer materials. The hydrophilic additives are easily precipitated during use, which makes the ultrafiltration membrane lack long-term stability. Therefore, the development of a polymer membrane material with higher selectivity and stability is a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of this, the present invention provides a polymer membrane material and a preparation method and application thereof. The polymer membrane material provided by the present invention has excellent selectivity and stability.

[0005] In order to solve the above technical problems, the present invention provides a polymer film material, comprising the following raw materials in percentage by weight: Film-forming polymer 10~18%; Vinyl monomer 0.1~22%; Initiator 0.1~3%; Coupling agent 0.1~22%; Organic solvent 35~89.7%; The alkenyl monomers include alkenyl hydrophilic monomers and alkenyl siloxy monomers.

[0006] Preferably, the mass ratio of the alkenyl hydrophilic monomer to the alkenyl siloxy monomer is 1-9:1-9; The alkenyl hydrophilic monomer includes one or more of ethyl vinyl ether, 2-hydroxyethyl methacrylate, N-vinyl formamide, 3-allyloxy-1,2-propylene glycol, N-vinyl pyrrolidone, glycidyl methacrylate, N-(hydroxymethyl) acrylamide, N-(hydroxyethyl) acrylamide and hydroxyethyl methacrylate; The alkenyl siloxy monomer includes one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(2-methoxyethoxy) silane and methyl vinyl dimethoxy silane.

[0007] Preferably, the coupling agent includes tetraethyl orthosilicate or triethoxysilane.

[0008] Preferably, the initiator is an oil-soluble azo initiator.

[0009] Preferably, the film-forming polymer comprises polyvinyl chloride, chlorinated polyvinyl chloride, polyvinylidene fluoride, polysulfone or polyethersulfone; The organic solvent includes dimethylformamide, dimethyl sulfoxide or dimethylacetamide.

[0010] The present invention also provides a method for preparing the polymer film material described in the above technical solution, comprising the following steps: Mixing a film-forming polymer, an olefin monomer, an initiator, a coupling agent and an organic solvent, and performing in-situ polymerization to obtain a film casting solution; After the casting solution is formed into a film, it is immersed in a coagulation bath for solidification to obtain the polymer film material.

[0011] Preferably, the mixing comprises the following steps: first dissolving a film-forming polymer in an organic solvent to obtain a film-forming polymer solution; The olefin monomer is dissolved in the film-forming polymer solution for the second time, and then mixed with the initiator and the coupling agent for the first time to obtain the film casting solution.

[0012] Preferably, the in-situ polymerization is carried out at a temperature of 50 to 90° C. and for a time of 4 to 48 hours.

[0013] Preferably, the coagulation bath comprises a sodium hydroxide solution or a hydrochloric acid solution; The mass concentration of the coagulation bath is 0.1-20%; The temperature of the coagulation bath is 20-70°C.

[0014] The present invention also provides the use of the polymer membrane material described in the above technical solution or the polymer membrane material prepared by the preparation method described in the above technical solution as an ultrafiltration membrane.

[0015] The present invention provides a polymer membrane material, comprising the following raw materials in percentage by weight: 10-18% of a film-forming polymer, 0.1-22% of an olefinic monomer, 0.1-3% of an initiator, 0.1-22% of a coupling agent and 35-89.7% of an organic solvent; the olefinic monomer comprises an olefinic hydrophilic monomer and an olefinic siloxy monomer. In the present invention, the olefinic monomer forms a functional polymer through in-situ polymerization, and the polymer formed by the in-situ polymerization and the film-forming polymer are physically entangled, thereby improving the hydrophilicity and antifouling properties of the polymer membrane material while improving its stability. At the same time, the coupling agent is pre-embedded in the casting liquid as an anchor point for subsequent reactions. During the phase separation and curing process, the coupling agent can be used as a uniformly distributed "network node" to quickly couple and crosslink through chemical action, and the covalent force is used as the internal driving force to inhibit segregation, so that the hydrophilic modifier that is easy to segregate and dissolve is locked in the polymer membrane, thereby improving the selectivity of the polymer membrane material.

[0016] The present invention also provides a method for preparing the polymer membrane material described in the above technical solution, comprising the following steps: mixing a film-forming polymer, an olefinic monomer, an initiator, a coupling agent and an organic solvent, and performing in-situ polymerization to obtain a casting liquid; and immersing the casting liquid in a coagulation bath for solidification after pre-filming to obtain the polymer membrane material. The present invention uses the in-situ polymerization initiated to coordinate the synchronous dissolution and entanglement of the film-forming polymer, and the added coupling agent is used as a fulcrum for chemical bonding during the phase separation process to effectively control the segregation and slow-release behavior of the modified additive (polymer generated by in-situ polymerization), and uses highly active coupling chemistry to firmly "lock" it in the separation membrane, thereby achieving a one-step method to achieve simultaneous improvement of the permeability, selectivity and lasting hydrophilicity of the ultrafiltration membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the principle of preparing polymer membrane materials; Figure 2 It is a dotted line graph of the pore size distribution of the membrane materials prepared in Examples 6 to 9 and Comparative Examples 1 to 2; Figure 3 It is the Fourier infrared spectra of the membrane materials prepared in Example 8 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0018] The present invention provides a polymer film material, comprising the following raw materials in percentage by weight: Film-forming polymer 10~18%; Vinyl monomer 0.1~22%; Initiator 0.1~3%; Coupling agent 0.1~22%; Organic solvent 35~89.7%; The alkenyl monomers include alkenyl hydrophilic monomers and alkenyl siloxy monomers.

[0019] In terms of mass percentage, the polymer film material provided by the present invention includes 10-18% of a film-forming polymer, which may be 12-16%. As a specific embodiment of the present invention, the film-forming polymer includes polyvinyl chloride, chlorinated polyvinyl chloride, polyvinylidene fluoride, polysulfone or polyethersulfone.

[0020] In terms of mass percentage, the polymer film material provided by the present invention includes 0.1-22% alkenyl monomer, which may be 3-12%, 6-10%, or 7-8%. As a specific embodiment of the present invention, the alkenyl monomer includes an alkenyl hydrophilic monomer and an alkenyl siloxy monomer, and the mass ratio of the alkenyl hydrophilic monomer to the alkenyl siloxy monomer may be 1-9:1-9, and may be specifically 1:1, 2:1, 3:1, 2:8, 1:9 or 9:1. As a specific embodiment of the present invention, the alkenyl hydrophilic monomer may include one or more of ethyl vinyl ether, 2-hydroxyethyl methacrylate, N-vinyl formamide, 3-allyloxy-1,2-propylene glycol, N-vinyl pyrrolidone, glycidyl methacrylate, N-(hydroxymethyl) acrylamide, N-(hydroxyethyl) acrylamide and hydroxyethyl methacrylate; specifically glycidyl methacrylate, N-vinyl pyrrolidone, ethyl vinyl ether, 3-allyloxy-1,2-propylene glycol or 2-hydroxyethyl methacrylate. As a specific embodiment of the present invention, the alkenyl siloxy monomer may include one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(2-methoxyethoxy) silane and methyl vinyl dimethoxy silane, specifically vinyl trimethoxy silane. In the present invention, the alkenyl siloxy monomer contains a highly active coupling group siloxy group; the alkenyl part in the alkenyl siloxy monomer can undergo in-situ free radical polymerization with an alkenyl hydrophilic monomer; and the siloxy functional group in the alkenyl siloxy monomer can undergo self-polymerization or cross-linking with a coupling agent.

[0021] In terms of mass percentage, the polymer film material provided by the present invention includes 0.1-3% initiator, which may be 0.5-2.2%, or 1-2%. As a specific embodiment of the present invention, the initiator may be an oil-soluble azo initiator, which may be azobisisobutyronitrile (AIBN).

[0022] In terms of mass percentage, the polymer film material provided by the present invention includes 0.1-22% coupling agent, which may be specifically 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20% or 22%. As a specific embodiment of the present invention, the coupling agent may include tetraethyl orthosilicate (TEOS) or triethoxysilane. In the present invention, the coupling agent contains two or more groups (siloxy groups) that can be cross-linked with the highly active coupling groups in the alkenylsiloxy monomer.

[0023] In terms of mass percentage, the polymer membrane material provided by the present invention includes 35-89.7% organic solvent, which may be 40-80%, or 67-75%. As a specific embodiment of the present invention, the organic solvent may include dimethylformamide, dimethyl sulfoxide, or dimethylacetamide (DMAc).

[0024] As a specific embodiment of the present invention, the thickness of the polymer membrane material can be 100-350 μm, or 200-300 μm; the pore size of the polymer membrane material can be 20-100 nm, or 24-40 nm; the pure water permeation flux of the polymer membrane material can be 50-2000 L·m -2 ·h -1 bar -1 , and can also be 100~410 L·m -2 ·h -1 bar -1 ; The polymer membrane material has a retention rate of more than 90% for 1.0 g / L bovine serum albumin; the surface water contact angle of the polymer membrane material is less than 90°, showing hydrophilicity.

[0025] The present invention also provides a method for preparing the polymer film material described in the above technical solution, comprising the following steps: Mixing a film-forming polymer, an olefin monomer, an initiator, a coupling agent and an organic solvent, and performing in-situ polymerization to obtain a film casting solution; The casting solution is pre-filmed and then immersed in a coagulation bath for solidification to obtain the polymer film material.

[0026] The present invention mixes a film-forming polymer, an olefinic monomer, an initiator, a coupling agent and an organic solvent, and performs in-situ polymerization to obtain a casting solution. As a specific embodiment of the present invention, the mixing may include the following steps: first dissolving a film-forming polymer in an organic solvent to obtain a film-forming polymer solution; The olefin monomer is dissolved in the film-forming polymer solution for the second time, and then mixed with the initiator and the coupling agent for the first time to obtain the film casting solution.

[0027] The present invention first dissolves the film-forming polymer in an organic solvent to obtain a film-forming polymer solution. As a specific embodiment of the present invention, the film-forming polymer may be dried before the dissolution; the moisture content of the film-forming polymer after drying may be less than 0.1%. As a specific embodiment of the present invention, the first dissolution may be carried out under stirring, and the stirring temperature may be 50-90°C, or 60-80°C; the stirring speed may be 200-400r / min, or 300-350r / min; the stirring time may be 4-48h, or 10-40h, or further 20-30h.

[0028] After obtaining the film-forming polymer solution, the present invention dissolves the olefinic monomer in the film-forming polymer solution for the second time and then mixes it with the initiator and the coupling agent for the first time to obtain the casting solution. As a specific embodiment of the present invention, the second dissolution can be carried out under stirring, and the stirring temperature can be 50~90°C, or 60~80°C; the stirring speed can be 200~400r / min, or 300~350r / min; the stirring time can be 4~48h, or 5~40h, or further 10~15h. As a specific embodiment of the present invention, the second dissolution can be carried out under a protective atmosphere, and the protective atmosphere can be a nitrogen atmosphere.

[0029] As a specific embodiment of the present invention, the first mixing can be carried out under stirring conditions, the stirring temperature can be 50-90°C, and can also be 60-80°C; the stirring speed can be 200-400r / min, and can also be 300-350r / min; the present invention has no special requirements for the stirring time, as long as it can be mixed evenly. As a specific embodiment of the present invention, the first mixing can be carried out under a protective atmosphere, and the protective atmosphere can be a nitrogen atmosphere.

[0030] As a specific embodiment of the present invention, the temperature of the in-situ polymerization can be 50-90°C, specifically 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C; the time of the in-situ polymerization can be 4-48h, specifically 5h, 10h, 15h, 20h, 25h, 30h, 35h, 40h or 45h. As a specific embodiment of the present invention, the in-situ polymerization can be carried out under a protective atmosphere, and the protective atmosphere can be a nitrogen atmosphere.

[0031] After obtaining the casting liquid, the present invention pre-films the casting liquid and then immerses it in a coagulation bath for solidification to obtain the polymer film material. As a specific embodiment of the present invention, the pre-filming can be performed by scraping the casting liquid on the surface of the substrate with a scraper and then pre-evaporating; the substrate can be a glass plate; the pre-evaporation can be performed by placing the scraped product in the air for 20 to 35 seconds.

[0032] As a specific embodiment of the present invention, the coagulation bath may include a sodium hydroxide solution or a hydrochloric acid solution; the mass concentration of the coagulation bath may be 0.1-20%, 1-15%, or 5-10%; the temperature of the coagulation bath may be 20-70°C, 25-65°C, or 30-60°C; the immersion time may be 10-60 min, 20-50 min, or 30-40 min.

[0033] As a specific embodiment of the present invention, after the curing, the process may further include: drying the film material obtained by the curing to obtain the polymer film material; the drying temperature may be 30-50°C, or 35-40°C; the drying time may be 40-50h, or 45-48h.

[0034] The schematic diagram of the principle of preparing the polymer membrane material of the present invention is as follows Figure 1 As shown, it is specifically dissolved synchronous in-situ polymerization: the film-forming polymer, alkenyl hydrophilic monomer, alkenyl siloxy monomer, coupling agent, initiator and organic solvent are mixed and polymerized, and the newly generated copolymer of alkenyl hydrophilic monomer and alkenyl siloxy monomer is entangled with the long chain of the film-forming polymer to form a uniform and compatible casting solution; at the same time, the coupling agent as the anchor point of the subsequent reaction is dissolved synchronously and evenly distributed in the casting solution, that is, dissolved synchronous in-situ polymerization. Highly active coupling synergistic film formation: after obtaining a uniform casting solution, the ultrafiltration membrane is prepared by a non-solvent induced phase separation method. The non-solvent can quickly induce the coupling and bonding of the highly active sites in the casting solution. With the coupling agent as the connecting fulcrum, the in-situ polymer chain segments are quickly and stably bonded through chemical bonds. The coupling and bonding in the phase separation film formation process (cross-linking of the coupling agent and the siloxy groups in the polymer formed by in-situ polymerization) is used to form a regular polymer network structure, constrain the movement of the polymer long chain, and efficiently construct an ultrafiltration membrane with relatively uniform pores, that is, highly active coupling synergistic film formation.

[0035] The present invention pre-dissolves easily dispersible small molecule coupling agents in the casting solution, and these coupling agents are evenly distributed in the casting solution until the phase separation process. Under the induction of the non-solvent, these "pre-embedded" small molecule coupling agents use them as the fulcrum for constructing the polymer cross-linking network, and regulate the surface segregation behavior in a chemical bonding manner. This "internal driving force" from the inside of the separation membrane matrix facilitates the more regular distribution of the additives in the polymer membrane, so that the random phase separation process is constrained and regularly arranged at the microscopic level, that is, the high-activity coupling synergistic phase separation constructs the separation membrane, and regulates its film formation process. The present invention has a certain universality for the currently commonly used wet-process membrane materials, and does not require the polymer materials used to have reaction sites, but through the free radical polymerization of olefin monomers, while the polymer membrane material is dissolved, the chain growth is carried out in situ and the chain entanglement occurs with it, that is, dissolution and synchronous in situ polymerization; after it forms a stable solution system, the polymer solution (nascent eco-membrane) is placed in a coagulation bath, and the coupling crosslinking between the in situ polymerized copolymer and the coupling agent is fully initiated by the coagulation bath. In the process of phase separation, the pore size distribution range of the polymer membrane material is reduced and its separation performance is improved by constraining and regulating the segregation behavior of the copolymer additives. At the same time, the phase separation process is induced by chemical cross-linking to achieve the preparation of highly selective hydrophilic biological separation ultrafiltration membranes.

[0036] The preparation method provided by the present invention has high reaction efficiency and mild conditions, reduces the time cost of additive synthesis, and has a controllable reaction process, and can finely regulate the performance of polymer membrane materials. The present invention can provide a rich active reaction site for the finished ultrafiltration membrane through the flexible selection of olefinic monomers, facilitating its subsequent post-modification for its specific application field.

[0037] The present invention realizes the preparation and modification of a hydrophilic ultrafiltration membrane by a one-step method, not only completing the in-situ preparation of a functionalized modifier, but also regulating the precipitation behavior of the modifier by a coupling agent, thereby achieving high selectivity (R BSA The preparation method provided by the present invention is universal and applicable to most common membrane-forming polymers on the market.

[0038] The present invention also provides the use of the polymer membrane material described in the above technical solution or the polymer membrane material prepared by the preparation method described in the above technical solution as an ultrafiltration membrane.

[0039] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0040] Example 1

[0041] The film-forming polymer is polyvinylidene fluoride, the organic solvent is dimethylacetamide (DMAc), the alkenyl hydrophilic monomer is glycidyl methacrylate, the alkenyl siloxy monomer is vinyl trimethoxy silane, the initiator is azobisisobutyronitrile (AIBN), and the coupling agent is tetraethyl orthosilicate (TEOS), and the preparation is carried out by the following steps: S1. Dissolve 16.0 wt% of dry polyvinylidene fluoride (8 g, water content less than 0.1%) in 75.8 wt% of DMAc (37.9 g) by stirring at 60°C for 4 h at a stirring speed of 300 r / min to obtain a uniformly dissolved film-forming polymer solution.

[0042] S2, dissolving 6 wt% of vinyl monomer glycidyl methacrylate (1.5 g) and vinyl trimethoxysilane (1.5 g) in a mass ratio of 1:1 in the membrane polymer material solution prepared in step S1, and 2 After stirring and dissolving under N atmosphere (stirring temperature was 60°C, stirring time was 5h, stirring speed was 300r / min), 1wt% (0.5g) of AIBN and 1.2wt% (0.6g) of TEOS were added, stirred evenly at 60°C and 300r / min, and then heated at 80°C and N 2 The in-situ polymerization reaction was carried out under the atmosphere for 20 hours to obtain a casting solution.

[0043] S3. Use a 250 μm scraper to scrape the casting liquid obtained in step S2 onto a dry glass plate, place it in the air for 30 seconds for pre-evaporation, and then place it in a hydrochloric acid solution coagulation bath with a pH value of 3 at room temperature (25°C) for phase separation (immersion time is 10 minutes). After complete solidification, transfer the obtained ultrafiltration membrane to deionized water for storage; take part of the ultrafiltration membrane and vacuum dry it in an oven at 40°C for 48 hours to obtain a polymer membrane material.

[0044] Example 2

[0045] The film-forming polymer is polyvinylidene fluoride, the organic solvent is dimethylacetamide (DMAc), the alkenyl hydrophilic monomer is N-vinyl pyrrolidone, the alkenyl siloxy monomer is vinyl trimethoxy silane, the initiator is azobisisobutyronitrile (AIBN), and the coupling agent is tetraethyl orthosilicate (TEOS), and the preparation is carried out by the following steps: S1. Dissolve 16 wt % dry polyvinylidene fluoride (8 g, water content less than 0.1%) in 71 wt % DMAc (35.5 g) by stirring at 60° C. for 4 h at a stirring speed of 300 r / min to obtain a uniformly dissolved film-forming polymer solution.

[0046] S2, dissolving 10 wt% of vinyl monomer N-vinyl pyrrolidone (3.33 g) and vinyl trimethoxysilane (1.67 g) in a mass ratio of 2:1 in the membrane polymer material solution prepared in step S1, and 2 After stirring and dissolving under N atmosphere (stirring temperature was 60°C, stirring time was 5h, stirring speed was 300r / min), 1wt% (0.5g) of AIBN and 2wt% (1g) of TEOS were added, stirred evenly at 60°C and 300r / min, and then heated at 80°C and N 2 The in-situ polymerization reaction was carried out under the atmosphere for 20 hours to obtain a casting solution.

[0047] S3. Use a 250 μm scraper to scrape the casting liquid obtained in step S2 onto a dry glass plate, place it in the air for 30 seconds for pre-evaporation, and then place it in a coagulation bath of a hydrochloric acid solution with a pH value of 5 at room temperature (25°C) for phase separation (immersion time is 20 minutes). After complete solidification, transfer the obtained ultrafiltration membrane to deionized water for storage; take part of the ultrafiltration membrane and vacuum dry it in an oven at 40°C for 48 hours to obtain a polymer membrane material.

[0048] Example 3

[0049] The film-forming polymer is polyvinylidene fluoride, the organic solvent is dimethylacetamide (DMAc), the alkenyl hydrophilic monomer is ethyl vinyl ether, the alkenyl siloxy monomer is vinyl trimethoxy silane, the initiator is azobisisobutyronitrile (AIBN), and the coupling agent is tetraethyl orthosilicate (TEOS), and the preparation is carried out by the following steps: S1. 16 wt % dry polyvinylidene fluoride (8 g, water content less than 0.1%) was stirred and dissolved in 71.8 wt % DMAc (35.9 g) at a stirring temperature of 60° C., a stirring time of 4 h, and a stirring speed of 300 r / min to obtain a uniformly dissolved film-forming polymer solution.

[0050] S2, dissolving 8 wt % of ethyl vinyl ether (3 g) and vinyl trimethoxysilane (1 g) in the membrane polymer material solution prepared in step S1 at a mass ratio of 3:1, and 2 After stirring and dissolving under N atmosphere (stirring temperature was 60°C, stirring time was 5h, stirring speed was 300r / min), 1wt% (0.5g) of AIBN and 3.2wt% (1.6g) of TEOS were added, stirred evenly at 60°C and 300r / min, and then heated at 80°C and N 2 The in-situ polymerization reaction was carried out under the atmosphere for 20 hours to obtain a casting solution.

[0051] S3. Use a 250 μm scraper to apply the casting solution obtained in step S2 onto a dry glass plate, place it in the air for 30 seconds for pre-evaporation, and then place it in a coagulation bath of deionized water with a pH value of 7 at room temperature (25°C) for phase separation. After complete solidification, transfer the obtained ultrafiltration membrane to deionized water for storage; take part of the ultrafiltration membrane and vacuum dry it in an oven at 40°C for 48 hours to obtain a polymer membrane material.

[0052] Example 4

[0053] The film-forming polymer is polyvinylidene fluoride, the organic solvent is dimethylacetamide (DMAc), the alkenyl hydrophilic monomer is 3-allyloxy-1,2-propanediol, the alkenyl siloxy monomer is vinyltrimethoxysilane, the initiator is azobisisobutyronitrile (AIBN), and the coupling agent is tetraethyl orthosilicate (TEOS), and the preparation is carried out by the following steps: S1. Dissolve 16 wt % dry polyvinylidene fluoride (8 g, water content less than 0.1%) in 65 wt % DMAc (32.5 g) by stirring at 60° C. for 4 h at a stirring speed of 300 r / min to obtain a uniformly dissolved film-forming polymer solution.

[0054] S2, dissolving 12 wt % of ethylenic monomer 3-allyloxy-1,2-propanediol (4 g) and vinyltrimethoxysilane (2 g) in a mass ratio of 2:1 in the membrane polymer material solution prepared in step S1, and 2 After stirring and dissolving under N atmosphere (stirring temperature was 60°C, stirring time was 5h, stirring speed was 300r / min), 1wt% (0.5g) of AIBN and 6wt% (3g) of TEOS were added, stirred evenly at 60°C and 300r / min, and then heated at 80°C and N 2 The in-situ polymerization reaction was carried out under the atmosphere for 20 hours to obtain a casting solution.

[0055] S3. Use a 250 μm scraper to scrape the casting liquid obtained in step S2 onto a dry glass plate, place it in the air for 30 seconds for pre-evaporation, and then place it in a coagulation bath of a sodium hydroxide solution with a pH value of 11 at room temperature (25°C) for phase separation. After complete solidification, transfer the obtained ultrafiltration membrane to deionized water for storage; take a part of the ultrafiltration membrane and vacuum dry it in an oven at 40°C for 48 hours to obtain a polymer membrane material.

[0056] Example 5

[0057] The film-forming polymer is polyvinylidene fluoride, the organic solvent is dimethylacetamide (DMAc), the alkenyl hydrophilic monomer is 2-hydroxyethyl methacrylate, the alkenyl siloxy monomer is vinyl trimethoxy silane, the initiator is azobisisobutyronitrile (AIBN), and the coupling agent is tetraethyl orthosilicate (TEOS), and the preparation is carried out by the following steps: S1. 16 wt % dry polyvinylidene fluoride (8 g, water content less than 0.1%) was stirred and dissolved in 74.6 wt % DMAc (37.3 g) at a stirring temperature of 60° C., a stirring time of 4 h, and a stirring speed of 300 r / min to obtain a uniformly dissolved film-forming polymer solution.

[0058] S2, dissolving 7 wt % of ethylenic monomer 2-hydroxyethyl methacrylate (2.33 g) and vinyl trimethoxysilane (1.17 g) in a mass ratio of 2:1 in the membrane polymer material solution prepared in step S1, and 2 After stirring and dissolving under N atmosphere (stirring temperature was 60°C, stirring time was 5h, stirring speed was 300r / min), 1wt% (0.5g) of AIBN and 1.4wt% (0.7g) of TEOS were added, stirred evenly at 60°C and 300r / min, and then heated at 80°C and N 2 The in-situ polymerization reaction was carried out under the atmosphere for 20 hours to obtain a casting solution.

[0059] S3. Use a 250 μm scraper to apply the casting solution obtained in step S2 onto a dry glass plate, place it in the air for 30 seconds for pre-evaporation, and then place it in a sodium hydroxide solution with a pH value of 10 at room temperature (25°C) for phase separation. After complete solidification, transfer the obtained ultrafiltration membrane to deionized water for storage; take a part of the ultrafiltration membrane and vacuum dry it in an oven at 40°C for 48 hours to obtain a polymer membrane material.

[0060] Example 6

[0061] The film-forming polymer is polyvinylidene fluoride, the organic solvent is dimethylacetamide (DMAc), the alkenyl hydrophilic monomer is 2-hydroxyethyl methacrylate, the alkenyl siloxy monomer is vinyl trimethoxy silane, the initiator is azobisisobutyronitrile (AIBN), and the coupling agent is tetraethyl orthosilicate (TEOS), and the preparation is carried out by the following steps: S1. 16 wt % dry polyvinylidene fluoride (8 g, water content less than 0.1%) was stirred and dissolved in 78.5 wt % DMAc (39.25 g) at a stirring temperature of 60° C., a stirring time of 4 h, and a stirring speed of 300 r / min to obtain a uniformly dissolved film-forming polymer solution.

[0062] S2, dissolving 3 wt % of ethylenic monomer 2-hydroxyethyl methacrylate (1 g) and vinyl trimethoxysilane (0.5 g) in a mass ratio of 2:1 in the membrane polymer material solution prepared in step S1, and 2 After stirring and dissolving under N atmosphere (stirring temperature was 60°C, stirring time was 5h, stirring speed was 300r / min), 1wt% (0.5g) of AIBN and 1.5wt% (0.75g) of TEOS were added, stirred evenly at 60°C and 300r / min, and then heated at 80°C and N 2 The in-situ polymerization reaction was carried out under the atmosphere for 20 hours to obtain a casting solution.

[0063] S3. Use a 250 μm scraper to scrape the casting liquid obtained in step S2 onto a dry glass plate, place it in the air for 30 seconds for pre-evaporation, and then place it in a coagulation bath of deionized water with a pH value of 7 at room temperature (25°C) for phase separation. After complete solidification, transfer the obtained ultrafiltration membrane to deionized water for storage; take part of the ultrafiltration membrane and vacuum dry it in an oven at 40°C for 48 hours to obtain a polymer membrane material, recorded as M2.

[0064] Example 7

[0065] A polymer film material was prepared according to the method of Example 6, except that the mass percentage of polyvinylidene fluoride was 16wt%, the weight percentage of DMAc was 74wt%, the added amount of 2-hydroxyethyl methacrylate was 2g, the added amount of vinyltrimethoxysilane was 1g, the total mass percentage of olefinic monomers was 6wt%, the total mass percentage of TEOS was 3wt%, the mass percentage of AIBN was 1wt%, and the prepared polymer film material was recorded as M3.

[0066] Example 8

[0067] A polymer membrane material was prepared according to the method of Example 6, except that the mass percentage of polyvinylidene fluoride was 16wt%, the weight percentage of DMAc was 69.5wt%, the added amount of 2-hydroxyethyl methacrylate was 3g, the added amount of vinyltrimethoxysilane was 1.5g, the total mass percentage of olefinic monomers was 9wt%, the total mass percentage of TEOS was 4.5wt%, the mass percentage of AIBN was 1wt%, and the prepared polymer membrane material was recorded as M4.

[0068] Example 9

[0069] A polymer membrane material was prepared according to the method of Example 6, except that the mass percentage of polyvinylidene fluoride was 16wt%, the weight percentage of DMAc was 65wt%, the total mass percentage of 2-hydroxyethyl methacrylate (4g) and vinyltrimethoxysilane (2g) was 12wt%, the mass percentage of TEOS was 6wt%, and the mass percentage of AIBN was 1wt%. The prepared polymer membrane material was recorded as M5.

[0070] Comparative Example 1 (without vinyl monomer, initiator, coupling agent)

[0071] S1. 8 g of dry polyvinylidene fluoride (water content less than 0.1%) was stirred and dissolved in 42 g of DMAc at a stirring temperature of 60°C, a stirring time of 4 h, and a stirring speed of 300 r / min to obtain a uniformly dissolved casting solution.

[0072] S2. Use a 250 μm scraper to scrape the casting liquid obtained in step S1 onto a dry glass plate, place it in the air for 30 seconds for pre-evaporation, and then place it in a coagulation bath of deionized water with a pH value of 7 at room temperature (25°C) for phase separation. After complete solidification, transfer the obtained ultrafiltration membrane to deionized water for storage; take part of the ultrafiltration membrane and vacuum dry it in an oven at 40°C for 48 hours to obtain a membrane material, which is recorded as M0.

[0073] Comparative Example 2 (without coupling agent)

[0074] S1. 8 g of dry polyvinylidene fluoride (water content less than 0.1%) was stirred and dissolved in 37 g of DMAc at a stirring temperature of 60°C, a stirring time of 4 h, and a stirring speed of 300 r / min to obtain a uniformly dissolved film-forming polymer solution.

[0075] S2, dissolving 2-hydroxyethyl methacrylate (3 g) and vinyl trimethoxysilane (1.5 g) in a mass ratio of 2:1 in the membrane polymer material solution prepared in step S1, and 2 After stirring and dissolving under N atmosphere (stirring temperature: 60℃, stirring time: 5h, stirring speed: 300r / min), 0.5g of AIBN was added, stirred evenly at 60℃ and 300r / min, and then heated at 80℃ and N 2 The in-situ polymerization reaction was carried out under the atmosphere for 20 hours to obtain a casting solution.

[0076] S3. Use a 250 μm scraper to apply the casting solution obtained in step S2 onto a dry glass plate, place it in the air for 30 seconds for pre-evaporation, and then place it in a coagulation bath of deionized water with a pH value of 7 at room temperature (25°C) for phase separation. After complete solidification, transfer the obtained ultrafiltration membrane to deionized water for storage; take a part of the ultrafiltration membrane and vacuum dry it in an oven at 40°C for 48 hours to obtain a polymer membrane material, recorded as M1.

[0077] The membrane materials prepared in Examples 6 to 9 and Comparative Examples 1 to 2 were tested for pore size distribution, and a pore size distribution point line graph was drawn, as shown in FIG. Figure 2 As shown; and the pore sizes are listed in Table 1.

[0078] The film materials prepared in Example 8 and Comparative Examples 1-2 were subjected to infrared detection to obtain Fourier infrared spectra. Figure 3 shown.

[0079] The flux and bovine serum albumin retention rate of the membrane materials prepared in Examples 1 to 9 and Comparative Examples 1 to 2 were tested according to GB / T 32360-2015 and the ultrafiltration membrane test method, and the results are shown in Table 1. The water contact angle of the membrane materials prepared in Examples 1 to 9 and Comparative Examples 1 to 2 and the membrane materials after being immersed in deionized water for 200 hours were tested using a fully automatic contact angle meter, and the results are shown in Table 1.

[0080] Table 1 Properties of membrane materials prepared in Examples 1 to 9 and Comparative Examples 1 to 2

[0081] Combining Table 1 and Figure 2 It can be seen that with the increase of the amount of coupling agent added, the pore size distribution of M1 to M5 becomes narrower, but since there is no coupling agent introduced into M1, the copolymer additive generated by in-situ polymerization has segregation and precipitation in the phase separation, which is manifested as Figure 2 The pore size distribution range shown in the figure increases significantly, and for M2 to M5, the presence of preloaded coupling agent effectively prevents the precipitation of copolymers during the phase separation process. As the amount of coupling agent added increases, the polymer cross-linking network is continuously improved, and the uniformity of pore size distribution is continuously improved, which shows that this highly active coupling-induced phase separation method can provide a highly selective membrane with uniform pore size.

[0082] Figure 3 Medium 1750cm -1 The characteristic absorption peak representing the carbonyl group becomes stronger after the coupling agent is added. This further demonstrates that when the amount of in-situ polymerized copolymer added remains unchanged, the preload of the coupling agent can anchor the copolymer by chemical bonding, restricting its precipitation behavior, so that the ultrafiltration membrane maintains high selectivity while being hydrophilically modified.

[0083] It can be seen from the performance parameters of pure water flux, bovine serum albumin retention rate and water contact angle in Table 1 that the covalent force between the coupling agent and the copolymer additive generated by in-situ polymerization stably confines it to the separation membrane, achieving a lasting improvement in hydrophilicity during the phase separation process while effectively inhibiting the formation of large pores on the surface of the separation membrane. The present invention successfully obtains a highly selective hydrophilic ultrafiltration membrane.

[0084] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A polymer film material, characterized in that: Including the following raw materials in percentage by weight: Film-forming polymer 10~18%; Vinyl monomer 0.1~22%; Initiator 0.1~3%; Coupling agent 0.1~22%; Organic solvent 35~89.7%; The alkenyl monomers include alkenyl hydrophilic monomers and alkenyl siloxy monomers.

2. The polymer film material according to claim 1, characterized in that: The mass ratio of the alkenyl hydrophilic monomer to the alkenyl siloxy monomer is 1-9:1-9; The alkenyl hydrophilic monomer includes one or more of ethyl vinyl ether, 2-hydroxyethyl methacrylate, N-vinyl formamide, 3-allyloxy-1,2-propylene glycol, N-vinyl pyrrolidone, glycidyl methacrylate, N-(hydroxymethyl) acrylamide, N-(hydroxyethyl) acrylamide and hydroxyethyl methacrylate; The alkenyl siloxy monomer includes one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(2-methoxyethoxy) silane and methyl vinyl dimethoxy silane.

3. The polymer film material according to claim 1, characterized in that: The coupling agent includes tetraethyl orthosilicate or triethoxysilane.

4. The polymer film material according to claim 1, characterized in that: The initiator is an oil-soluble azo initiator.

5. The polymer film material according to claim 1, characterized in that: The film-forming polymer includes polyvinyl chloride, chlorinated polyvinyl chloride, polyvinylidene fluoride, polysulfone or polyethersulfone; The organic solvent includes dimethylformamide, dimethyl sulfoxide or dimethylacetamide.

6. The method for preparing the polymer film material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Mixing a film-forming polymer, an olefin monomer, an initiator, a coupling agent and an organic solvent, and performing in-situ polymerization to obtain a film casting solution; The casting solution is pre-filmed and then immersed in a coagulation bath for solidification to obtain the polymer film material.

7. The method for preparing a polymer film material according to claim 6, characterized in that: The mixing comprises the following steps: first dissolving a film-forming polymer in an organic solvent to obtain a film-forming polymer solution; The olefin monomer is dissolved in the film-forming polymer solution for the second time, and then mixed with the initiator and the coupling agent for the first time to obtain the film casting solution.

8. The method for preparing a polymer film material according to claim 6 or 7, characterized in that: The in-situ polymerization is carried out at a temperature of 50-90° C. and for a time of 4-48 hours.

9. The method for preparing a polymer film material according to claim 6, characterized in that: The coagulation bath comprises a sodium hydroxide solution or a hydrochloric acid solution; The mass concentration of the coagulation bath is 0.1-20%; The temperature of the coagulation bath is 20-70°C.

10. Use of the polymer membrane material according to any one of claims 1 to 5 or the polymer membrane material prepared by the preparation method according to any one of claims 6 to 9 as an ultrafiltration membrane.

Citation Information

Patent Citations

  • Preparation method of synchronous cross-linking modified polyvinylidene fluoride microporous film

    CN103007786A

  • Dynamic-crosslinking preparation method of polyvinyl alcohol-blended hollow-fiber ultrafiltration membrane

    CN103349920A

  • PVDF permanently hydrophilic ultrafiltration membrane and modification method thereof

    CN104607063A

  • Preparation method of durable hydrophilic homogeneous-pore ultrafiltration membrane

    CN113578062A

  • Preparation method of durable hydrophilic ultrafiltration membrane

    CN117101420A

Cited By

  • Persistent super-hydrophobic uniform-pore separation membrane as well as preparation method and application thereof

    CN122006505A

  • A durable super-hydrophobic uniform-pore separation membrane and a preparation method and application thereof

    CN122006505B